Evaluación del comportamiento de la vegetación de páramo frente al calentamiento inducido experimentalmente en el ecosistema de páramo del Parque Nacional Podocarpus - Minga León, Saula Verónica (2014)
The present study focuses on a In situ heating experiment in the wilderness of the PNP- Sector Cajanuma accelerating climate change on a small scale for predicting responses of plant communities , in order to obtain long-term information for decision use decisions , management and conservation of the moor. For the artificial increase in temperature chambers open transparent polycarbonate, which were designed by the International Experience Tundra (ITEX) was used, these structures passively raise the temperature of 1-2 ° C (García, 2010). The pilot area consists of three peaks at different altitudinal gradients in top six plots each 1 m2, located 12 meters from the high point of the summit were installed addresses and the Northeast, East and Southeast, 3 of which were subjected to the heating and 3 used as control plots, giving a total of 18 plots (9 plots cameras and 9 control). In each plot were identified and quantified the percentage of coverage and number of individuals; temperature data, which will allow future studies to predict the behavior of these ecosystems at regional scales through comparative studies were also recorded. At the same time local adaptation strategies are proposed, based on the identification and prioritization of needs through the wasteland of the PNP. In all experimental treatment units (camera) and untreated (control), a total of 65 species in 47 genera and 33 families were recorded. Which is the most representative families Asteraceae , Ericaceae and Poaceae , while the species with the highest number of individuals is Disterigma acuminatum . With respect to the dominant vegetation category is vascular plants , it was established that all treatments plots both camera- based control plots altitude have high alpha diversity in an area of approximately 18 m2. For analysis of possible changes in the variable density versus altitude showed an increase in the number of individuals in the two treatments ( camera control) during the monitoring time , however it should be mentioned that in the plots with the camera increase was lower compared to the control plots , in terms of percentage cover and diversity alfa showed increases in the control plots, whereas plots with cameras percent cover and diversity decreased, probably because the temperature rise alter the normal behavior of biodiversity. For analysis of the three variables based on the orientation showed no marked trends. In terms of treatment and no treatment regardless of altitude and orientations. The data to date indicates that there are no statistically significant differences ie no heating a dramatic impact on the number of individuals (density), percentage of plant cover and diversity (Shannon index). Regarding the relationship between the aforementioned variables with temperature, there is some relationship between these variables, possibly for the short time monitoring. As for the design of strategies, these were defined toward the solution of problems encountered in the wilderness of the PNP.